2016
DOI: 10.19046/abp.v03i04.06
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on the phytochemical and pharmacological aspects of Podophyllum hexandrum: a high value medicinal plant

Abstract: Podophyllum hexandrum Royle, a rhizomatous perennial herb from the Berberidaceae family, is a highly reputed medicinal plant known for its lignan, podophyllotoxin. Podophyllotoxin and its semisynthetic derivativatives are potent anticancer agents. The semisynthetic analogues of podophyllotoxin are also used in the treatment of lung cancer, testicular cancer, neuroblastoma, hepatoma and other tumor diseases. While Podophyllotoxin acts as an inhibitor of the microtubule assembly, the cytotoxic action of its dere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It has been reported that the process of cancer development is closely linked to the biochemical processes of cell cycle and apoptosis. Currently, the drug discovery process focuses on chemotherapeutic agents which can target the cell cycle and apoptosis [9][10][11][12][13][14].…”
Section: Cells With Decreased λψMmentioning
confidence: 99%
“…It has been reported that the process of cancer development is closely linked to the biochemical processes of cell cycle and apoptosis. Currently, the drug discovery process focuses on chemotherapeutic agents which can target the cell cycle and apoptosis [9][10][11][12][13][14].…”
Section: Cells With Decreased λψMmentioning
confidence: 99%
“…Methylwogonin also inhibited cancer cell invasion in a dose-dependent manner. Previous studies have reported that the activation of the PI3K/AKT/mTOR pathway plays a vital role in ovarian cancer tumorigenesis, progression and chemotherapy resistance [27, 28]. Therefore we evaluated the effect of methylwogonin on this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Podophyllum is generally represented by three species including Podophyllum hexandrum, Podophyllum peltatum, and Podophyllum sikkimensis. Of these Podophyllum species, Podophyllum hexandrum Royle is medicinally more valuable, containing comparatively higher concentration of podophyllotoxin (Muzafar and Shajrul, 2016) [35] . P. hexandrum is a source of several physiologically significant metabolites with cytotoxic, antifungal, anti-inflammatory, antioxidant, and radioprotective properties (Prakash et al, 2005) [36] .…”
Section: Introductionmentioning
confidence: 99%